A Comparison of Incidence of Patient Aggression in the University Psychiatric Clinic Ljubljana and at the Department of Psychiatry of the University Medical Centre Maribor: Primerjava pojavnosti agresije bolnikov v Univerzitetni psihiatrični kliniki Ljubljana in na Oddelku za psihiatrijo Univerzitetnega kliničnega centra Maribor - Žgavec, Nace; Kores Plesničar, Blanka (Acta Medico-Biotechnica, 2021)
Purpose: Management of aggressive behaviour in patients with psychiatric diagnoses presents a challenge and burden for health staff. The present study compared two psychiatric institutions (the Department of Psychiatry of the University Medical Centre Maribor and the University Psychiatric Clinic Ljubljana) in terms of frequency and consequences of patient aggression. We compared frequencies of aggression between male and female patients, patients diagnosed with schizophrenia and other diagnoses, previously aggressive patients and patients who were aggressive for the first time. We also compared the use of special protective measures in both institutions.Methods: This study was retrospective and included the analysis of documentation of patients who were hospitalised at both institutions from 1 January 2012 to 31 June 2012. We identified patients with aggressive behaviour and acquired their sociodemographic data, diagnosis, number of hospitalisations, presence of alcohol or psychoactive substances and presence of aggressive behaviour. For assessment of aggressive behaviour, the Overt aggression scale was used. Results: One-hundred and forty-seven patients met the criteria for aggressive behaviour. There was no statistically significant difference in the frequency of aggression between genders or diagnoses. However, there was a statistically significant difference (p ≤ 0.01) in the frequency of aggression in patients who had previously been aggressive compared to those patients who had not exhibited such behaviour. There was no statistically significant difference in the use of special protective measures between the two institutions.Conclusions: Two hypotheses were confirmed: patients who had exhibited previous aggression were more frequently aggressive than those with no previous aggressive behaviour while the use of special protective measures between the two institutions was similar.
Keywords: Overt aggression scale; psychiatry; special protective measures; violence; aggression